Genomic annotation data for three Anthophora bee species - Taliadoros, Demetris; Soares, André E. R.; Borges Dias, Guilherme; Bunikis, Ignas; Pippel, Martin; Olsson, Anna; Mosbech, Mai-Britt; Heintz, Julia; Lager, Nina; Strand, Anna-Sofi; Pettersson, Mats; Vinnere Pettersson, Olga; et al. (Uppsala University, 2026)
This dataset contains IsoSeq transcripts, sequence repeat annotations, and estimates of genetic diversity and Tajima’s D across the genomes of three Anthophora bee species: A. quadrimaculata, A. retusa and A. plagiata.

A brief description of each file type is provided below. A detailed explanation of the methods used to generate the files can be found in the publication available via https://doi.org/10.1111/mec.70204.

IsoSeq transcripts:PacBio IsoSeq transcripts aligned to the primary genome assembly using miniprot v.0.10-r226. The raw IsoSeq data are deposited in the European Nucleotide Archive (ENA) under the accession numbers:

- A. quadrimaculata (iyAntQuad1), PRJEB72355
- A. plagiata (iyAntPlag1), PRJEB72356
- A. retusa (iyAntRet1), PRJEB72357
Files:

- Anthophora_plagiata_isoseq.gff
- Anthophora_retusa_isoseq.gff
- Anthophora_quadrimaculata_isoseq.gff
Repeats:Nucleotide sequences of the predicted repetitive elements in GFF format. Repeats were identified using RepeatModeler2.

Files:

- Anthophora_plagiata_repeats.gff
- Anthophora_retusa_repeats.gff
- Anthophora_quadrimaculata_repeats.gff
Nucleotide diversity Pi:Nucleotide diversity (π) was estimated in non-overlapping 5 kb windows across each genome using variant calls generated from population sequencing data from 57, 52, and 27 individuals for A. retusa, A. quadrimaculata, and A. plagiata, respectively. This estimate was calculated using vcftools v. 0.1.17. π reflects the average number of nucleotide differences per site between two randomly chosen sequences.

Files:

- plag_5kb.windowed.pi
- quad_5kb.windowed.pi
- retusa_5kb.windowed.pi
Tajimas’D:Tajima’s D was calculated in sliding windows across the genome using SNP datasets for each species using vcftools v. 0.1.17. Tajima’s D summarizes allele frequency spectra and can indicate departures from neutral evolution, such as population expansion, contraction, or selection.

Files:

- plagiata.Tajima.D.end_column_5kb_midpoint.bed
- quadri.Tajima.D.end_column_5kb_midpoint.bed
- retusa.Tajima.D.end_column_5kb_midpoint.drop_nan.bed
Available variables:For a description of the column headers in the GFF file format, please refer to the respective documentation: https://github.com/The-Sequence-Ontology/Specifications/blob/master/gff3.md
Keywords: Genomics and transcriptomics; Evolutionary ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi; Genetics and Genomics; Genetik och genomik